Perlindungan Ham Terhadap Kebocoran Data Pribadi Pasien Akibat Cyber Crime - Qotrunnada, Salsabilla Diva (Civiliza Publishing, Indonesia., 2023)
Advances in technology and information in Indonesia affect all aspects of life, which will continue to be accompanied by positive and negative impacts. The cause of cyber crime has several supporting factors, this crime certainly endangers the safety and privacy of victims, because all their data could be disseminated to the general public for various purposes. In writing this journal, we examine the protection of human rights in a case of data dissemination. personal consequences of cyber crime based on library research methods. So this research aims to provide insight into protecting human rights and preventing cyber crime attacks. Human rights should be fulfilled in terms of ensuring the privacy of their personal data, so that past events that are very detrimental to all parties should not be repeated. The regulations that are still in effect only refer to the ITE Law Number 11 of 2008 concerning Information and Electronic Transactions which is the legal basis for cybercrime cases. The government's role is needed to protect human rights which are threatened by cybercrime which is increasingly proliferating in the current era. Data that should not all be accessible to the public is instead spread freely due to the actions of hackers or individuals who commit cyber crimes. The government needs to plan more specific regulations in handling cyber crime cases.